Cross-Sectional and Longitudinal Associations Between the Serum G\lobulin Level, and Renal Impairment and All-Cause Deaths in Chinese Patients With Newly Diagnosed Multiple Myeloma - Cheng, Jun; Sun, Jia; Zhao, Yi; Li, Xiayu; Jiang, Yan; Lv, Rong; Li, Heng; Chen, Jianghua (Frontiers in Oncology, 2022)
Abstract Background: A large number of studies have shown that serum globulin plays an important role in a variety of cancers; However, few studies have identified the association between serum globulin levels and end-stage renal disease (ESRD) and all-cause death in Chinese patients with multiple myeloma (MM). Methods: A generalized additive model and smooth curve fitting were fitted to assess the cross-sectional relationship between the serum globulin levels and renal impairment (RI) at baseline. Multivariate-adjusted Cox regression models were performed to determine the associations between the baseline serum globulin levels and the onset of all-cause death and ESRD in patients with MM. Results: 288 participants who were followed for > 3 months were eligible for the retrospective study. The median serum globulin level was 5.1 ± 2.6 mg/dL. The average follow-up time was 23.3 months . Thirty-two patients (11.5%) had ESRD and 24 patients (8.33%) died after diagnosis. In patients with a serum globulin level < 6.1 mg/dL, the serum globulin level had an independent, negative correlation with the occurrence of MM-related RI. Patients were divided into three groups on the basis of serum globulin tertiles: low (L group), 3.3 mg/dL; middle (M group), 3.3–6.0 mg/dL; and high (H group), 6.0 mg/dL. Cox regression analysis showed that low serum globulin levels may be independent risk factors for all-cause death and the occurrence of ESRD in patients with MM; however, an elevated baseline serum globulin can predict all-cause deaths in patients with MM, but can not predict the oneset of ESRD. Conclusions: This observational study suggested that there was a non-linear relationship between the serum globulin level and the occurrence of RI in patients with MM. This finding showed that the serum globulin level had a U-shaped association with all-cause death and an L-shaped association with ESRD in patients with MM.